Impact of work engagement on turnover intention: moderation by psychological capital in India - Gupta, Manish; Shaheen, Musarrat (Business: Theory and Practice, 2017)
With increased number of employment opportunities in India, employers are increasingly finding it difficult to control employee turnover. Nonetheless, positive psychologists argue that one of the ways to face this challenge is by understanding the positive factors such as, work engagement and personal resources that negatively affect employees’ turnover intention. Therefore, the objective of this study is to examine the moderating role of psychological capital in the work engagement – employee turnover intention relationship. Hierarchical regression was used to analyze a sample of 228 employees working in diverse industries. The findings indicate that psychological capital moderates the relationship between work engagement and intention to turnover. The findings augment the theory of self and role by identifying moderating role of personal resources in strengthening the negative relationship between work engagement and turnover intention. Managers may take steps to enhance the employee-co-worker and employee-supervisor relationship either by promoting team related activities or by enabling their employees to work independently. Also, in order to save the cost of hiring a new candidate and losing an experienced employee, managers may create mechanisms for measuring work engagement of at least their key employees or a regular basis. This paper fulfils an identified need to study how psychological capital plays a key role in affecting the work engagement–employee turnover intention relationship in Indian context.